Simulating Electrohydrodynamic Ion-Drag Pumping on Distributed Parallel Computing Systems - Shakeel Ahmed, Kamboh; Zubair, Ahmed Kalhoro; Kashif, Ali Abro; Jane, Labadin (Indian Society for Education and Environment, 2017)
Objectives: This paper aims to simulate EHD ion-drag pumping model using Finite Difference Method (FDM) and to apply the idea of parallelism to reduce the computational time. Methods: The numerical simulation of EHD ion-drag pumping plays an important part not only to understand the different working principles but also enables to model the designs with better performance. Since the performance of EHD pumps depends on the shapes and geometries of the actuator electrodes, therefore the variation in the geometric dimensions of the electrodes require dense and fine meshes for numerical solution. Consequently, the numerical simulations take unacceptably more execution time on sequential computers. For that reason, a Data Parallel Algorithm for EHD model (DPA-EHD) is designed. To implement the parallel algorithm a distributed parallel computing system using MATLAB Distributed Computing Server (MDCS) is configured. The computational time and speedup with respect to the different number of processors is evaluated. Findings: This results show that the parallel algorithm for EHD simulations may provide 4.14 times more speedup over sequential algorithm for large grid sizes. Improvements: This study shows the feasibility of using the parallelism to reduce the computational time in the EHD model enabling to simulate the micropumps with very small dimensions of electrodes.